THE ENERGY CAPACITY OF AN AQUEOUS SOLUTION OF THE DRUG-STIMULATOR OF PLANT GROWTH - Mamonov A.G; Zhalgassuly N; Ismailova A.A (Academic Journal of Physical and Chemical Sciences, 2019)
Object of research is technology of formulation of physiologically active humic products, methods of aqueous solutions preparation and effectiveness of their impacts on seeds and sprouts of grain and vegetable crops, testing the product in rough soil and climatic conditions of the arid zone of Kazakhstan. Therefore, the purpose of paper is development of technology for formulation of preparation and agromethods of its use in order to increase agricultural crop yields in extreme soil and climatic conditions based on laboratory and field tests, biophysical monitoring, and main technological parameters adjustments. The results of testing experimental sample of the product formulated according to the developed technology and agromethods on various types of low-productive soils of arid zones of the republic are presented. Optimal concentrations of aqueous solutions of humic product for agricultural crops seeds treatment, optimal technological parameters to prepare seeds for sowing (duration of treatment with humic product, tempering, etc.) have been determined by the method of biotesting: optimal conditions for sowing seeds into soil (substrate moisture content, temperature, salinity) have been determined. Research has been carried out in laboratory conditions in winter and on experimental sites in several farms. As a result of executed work effectiveness of the product formulated according to the developed technology on low-productive soils with a salinity level of 0.8 2.2% was established. Increase in the yield of grain crops reaches 24.2 - 42.1%, rice 76.2 - 78.6%. and soybean - 34.8%.